2013
DOI: 10.4103/2153-3539.112686
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of telemedicine success in Africa

Abstract: The use of information and communication technologies (ICT) tools to improve the efficiency of professionalism at work is increasing every time under the dynamic digital environment. Tools such as telemedicine, tele-education, and health informatics have of late been incorporated in the health sector to enable easy access to essential services, for example, in medical areas from referral centers by the patients on one hand and enabling the doctor to doctor consultations for the benefit of patients. Unfortunate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 20 publications
0
58
0
1
Order By: Relevance
“…Another success factor for the acceptance of the approach is its feasibility and cost effectiveness, especially in rural areas and settings with financial limitations [21]. In this regard, we showed that a reasonable amount of time and technical resources were needed for initial setup and expansion of the network.…”
Section: Success Factors For Imaging Networkmentioning
confidence: 89%
“…Another success factor for the acceptance of the approach is its feasibility and cost effectiveness, especially in rural areas and settings with financial limitations [21]. In this regard, we showed that a reasonable amount of time and technical resources were needed for initial setup and expansion of the network.…”
Section: Success Factors For Imaging Networkmentioning
confidence: 89%
“…1–3 A recent International Telecommunication Union survey showed that prices of ICT hardware are decreasing and long-lasting batteries can now provide longer uninterrupted data collection periods. 4 …”
Section: Introductionmentioning
confidence: 99%
“…Despite considerable optimism about the potential value of eHealth and its components, such as telemedicine, [44,45] few reports have appraised aspects such as VFM and affordability. [46,47] Experience in the developing world shows that identifying and quantifying benefits within the implementation communities is necessary for the integration and sustainability of telemedicine and cautions about few studies having addressed this.…”
Section: The Role Of An African Ehi Appraisal Frameworkmentioning
confidence: 99%